Physical activity, screen viewing time, and overweight/obesity among Chinese children and adolescents: an update from the 2017 physical activity and fitness in China-the youth study - Zheng Zhu; Yan Tang; Jie Zhuang; Yang Liu; Xueping Wu; Yujun Cai; Lijuan Wang; Zhen-Bo Cao; Peijie Chen (BMC, 2019)
Abstract Background With increases in inactive lifestyles and mounting pressure for academic excellence in Chinese younger populations, lack of physical activity and increased prevalence of obesity have become a major public health concern in China. The purpose of this study is to provide updated estimates on the prevalence of meeting moderate-vigorous physical activity (MVPA) and screen viewing time guidelines, and overweight and obesity among Chinese school-aged children and adolescents, with a secondary aim examining variations in prevalence by sex, grade groupings, and residential location. Methods The study sample came from the 2017 Physical Activity and Fitness in China-The Youth Study, a cross-sectional and national survey of 131,859 students (aged 7 to 19 years) from 986 public schools in China. Measures of MVPA, screen viewing time, and age- and sex-specific overweight and obese body mass index were used to calculate national prevalence estimates of Chinese school-aged children and adolescents. Results In 2017, 34.1% (95% confidence interval [CI], 34.09-34.11%) of children and adolescents met MVPA guidelines and 65.4% (95% CI, 65.39-65.41%) adhered to screen viewing time guidelines. The prevalence of overweight and obesity was 15.1% (95% CI, 15.09-15.11%) and 10.7% (95% CI, 10.69-10.71%), respectively. Prevalence estimates differed by sex (boys, girls), grade grouping (primary schools, junior middle schools, junior high schools), and residential location (rural, urban). Conclusions There remains a low prevalence of meeting MVPA guidelines and high prevalence of overweight and obesity in Chinese school-aged children and adolescents. Future efforts should focus on monitoring the trend of these behavioral and health risk factors to inform school policies and programs aimed at increasing physical activity and reducing and preventing obesity in younger populations in China.